A new temnospondyl record from the Upper Triassic of Argentina - Marsicano, Claudia Alicia (2005)
The Brachyopoidea is a group of Mesozoic temnospondyls with flat, parabolic skulls that were recently reviewed and considered to include Brachyopoidea and Chigutisauridae (Warren and Marsicano, 2000; Yates and Warren, 2000, Damiani and Kitching, 2003). Brachyopids have been recorded from several different localities both in Gondwana (excluding South America) and Laurasia (Warren and Marsicano, 2000) during the Early-Middle Triassic. After the Middle Triassic, they areabsent from the fossil record for several million years until they are recorded in the Middle-Late Jurassic of China (Dong, 1985) and Mongolia (Shishkin, 1991). In contrast, chigutisaurid temnospondyls appear to be restricted to Gondwana. They are known from the Lower Triassic, Lower Jurassic and Lower Cretaceous of Australia (Warren, 1981; Warren and Hutchinson, 1983; Warren et al., 1997), the Upper Triassic of Argentina (Bonaparte, 1975; Marsicano, 1993, 1999) and India (Sengupta, 1995), and from the Upper Triassic and Lower Jurassic of South Africa (Warren and Damiani, 1999). This paper describes a new temnospondyl specimen consisting of an incomplete left mandible, preserved from the symphysis to the level of the anterior coronoid, found in strata assigned to the Late Triassic Cacheuta Formation at the Potrerillos locality in western Argentina (Marsicano et al., 2000). The mandible is here considered to be a putative brachyopid and, therefore, it would be the first occurrence of this group in South America and the youngest for Gondwana. Abbreviations-MCNAM-PV, Museo de Ciencias Naturales y Antropológicas Juan Cornelio Moyano of Mendoza (Argentina), paleovertebrados collection; UCMP, University of California Museum of Paleontology, Berkeley (USA).